Integral procedure to assess crack filling and mechanical contribution of polymer-based healing agent in encapsulation-based self-healing concrete. (March 2017) - Gilabert, F.A.; Van Tittelboom, K.; Van Stappen, J.; Cnudde, V.; De Belie, N.; Van Paepegem, W.
Abstract: This work presents an experimental and numerical study to analyze the crack filling process in encapsulation-based self-healing concrete. A specimen consisting of two small concrete blocks has been designed containing capsules filled with a polyurethane-based healing agent. This design enables to control the capsule breakage and release of healing agent. Two setups are studied: (i) a two-capsule system, where one capsule contains the pre-polymer fluid and the other contains a water-based accelerator component, and (ii) a single capsule system with only the pre-polymer fluid. The amount of healing agent released in the crack is visualized using micro Computed Tomography scanning. Tensile mechanical tests are performed to evaluate the strength contribution of the cured healing agent. A computational fluid dynamics model has been developed to understand how the healing agent spreads in the crack as a function of the crack width. Highlights: Integral procedure to analyze crack filling process of PU resin in encapsulation-based self-healing concrete. Specimen design provides control over the capsule breakage, crack opening distance and easy mechanical testing. Study comprises micro-CT technique, image analysis, tensile tests and CFD simulations. Two setups studied: sample with two capsules (resin+accelerator) and sample with one capsule (only resin). No foaming is produced but healed resin strength ranges between 1.2 MPa and 3.7 MPa, for crack spaces between 381  μ m and 50.8 μm, respectively.